2008
DOI: 10.1109/tbme.2008.923142
|View full text |Cite
|
Sign up to set email alerts
|

Robust Predictive Control Strategy Applied for Propofol Dosing Using BIS as a Controlled Variable During Anesthesia

Abstract: This paper presents the application of predictive control to drug dosing during anesthesia in patients undergoing surgery. The performance of a generic predictive control strategy in drug dosing control, with a previously reported anesthesia-specific control algorithm, has been evaluated. The robustness properties of the predictive controller are evaluated with respect to inter- and intrapatient variability. A single-input (propofol) single-output (bispectral index, BIS) model of the patient has been assumed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
152
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(160 citation statements)
references
References 19 publications
1
152
2
1
Order By: Relevance
“…However, due to the high complexity of this procedure an automated system for drug administration would be a good support for the clinicians (see Meijler [6]). The development of controllers for the automatic administration of drugs in patients has deserved the attention of several researchers and led to a number of contributions and controllers namely a predictive control in Ionescu et al [7], an adaptive model-based controller in Mortier et al [8] and Simanski et al [9], a PID in Padula et al [10], a neural in Ortolani et al [11], a fuzzy logic in Shieh et al [12], a model predictive control in Sawaguchi et al [13] and Chang et al [14], but in these contributions the control of the DoA is not fully automatic. More concretely, the administration of the hypnotic is made automatically, but the administration of the analgesic is manually made by a clinician.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high complexity of this procedure an automated system for drug administration would be a good support for the clinicians (see Meijler [6]). The development of controllers for the automatic administration of drugs in patients has deserved the attention of several researchers and led to a number of contributions and controllers namely a predictive control in Ionescu et al [7], an adaptive model-based controller in Mortier et al [8] and Simanski et al [9], a PID in Padula et al [10], a neural in Ortolani et al [11], a fuzzy logic in Shieh et al [12], a model predictive control in Sawaguchi et al [13] and Chang et al [14], but in these contributions the control of the DoA is not fully automatic. More concretely, the administration of the hypnotic is made automatically, but the administration of the analgesic is manually made by a clinician.…”
Section: Introductionmentioning
confidence: 99%
“…The results reported in this study suggest that the control performance has been shown to be more robust by 12% during induction phase as compared to the study in [4], where only Propofol was administered. The disturbance were not the same in both studies, so a performance comparison during maintenance is not possible.…”
Section: Limitations Of This Studymentioning
confidence: 43%
“…The inherent capability of MPC to outperform other control strategies has been already shown in [19,4] by means of simulations evaluating both the performance and the robustness of the closed loop system. In the general MPC scheme represented in Fig.…”
Section: Mpc-epsac Strategymentioning
confidence: 98%
See 2 more Smart Citations